Analisis Modul Ajar Operasi Hitung Bilangan Bulat pada SMP Kelas VII berdasarkan Praksiologi - Muhammad Fajar Anugrah; Tatang Suherman (Departement of Mathematics Education, 2022)
The development of teaching modules aims to provide teaching tools that can guide teachers in carrying out effective and efficient learning. with good teaching modules when the application process is in accordance with the discussion of the slogan indicators so that they are able to deliver students to the expected knowledge. This article presents an analysis of the module content reviewed from praxeological theory. Based on the analysis required several techniques that are not conveyed so that students' knowledge is limited. In the discussion, an alternative design has been given to the material for adding and subtracting integer operations in relation to everyday life based on the Didactical Situation Theory.